A novel ML domain-containing protein (SpMD2) functions as a potential LPS receptor involved in anti-Vibrio immune response. (February 2020) - Wang, Yue; Zhao, Shu; Zhang, Bin; Ma, Hong-Yu; Fang, Wen-Hong; Sheng, Wen-Quan; Yang, Li-Guo; Li, Xin-Cang
Abstract: The myeloid differentiation protein 2 (MD2)-related lipid-recognition (ML) proteins display diverse biological functions in host immunity and lipid metabolism by interacting with different lipids. Human MD2, an indispensable accessory protein in TLR4 signaling pathway, specifically recognizes lipopolysaccharides (LPS), thereby leading to the activation of TLR4 signaling pathway to produce many effectors that participate in inflammatory and immuneresponses against Gram-negative bacteria. Toll and immune deficiency (IMD) pathways are first characterized in Drosophila and are reportedly present in crustaceans, but the recognition and activation mechanism of these signaling pathways in crustaceans remains unclear. In the present study, a novel ML protein was characterized in mud crab ( Scylla paramamosain ) and designated as Sp MD2. The complete SpMD2 cDNA sequence is 1114 bp long with a 465 bp open reading frame; it encodes a protein that contains 154 amino acids (aa). In the deduced protein, a signal peptide (1–21 aa residues) and a ML domain (43–151 aa residues) were predicted. Sp MD2 shared a similar three-dimensional structure and a close evolutionary relationship with human MD2. SpMD2 was highly expressed in gills, hemocytes, intestine, and hepatopancreas and was upregulated in gills and hemocytes after challenges with bacteria, thereby suggesting its involvement in antibacterial defense. Western blot assay showed that Sp MD2 possesses strong binding activities to different bacteria and two fungi. ELISA demonstrated that Sp MD2 exhibits binding abilities to LPS, lipid A, peptidoglycan (PGN), and lipoteichoic acid (LTA). Its binding ability to LPS and lipid A were stronger than to PGN or LTA, implying that Sp MD2 was an important LPS-binding protein in mud crab. Bacterial clearance assay revealed that the pre-incubation of Vibrio parahemolyticus with Sp MD2 facilitates bacterial clearance in vivo and that knockdown of SpMD2 dramatically suppresses the bacterial clearance and decreases the expression of several antimicrobial peptides (AMPs). Furthermore, Sp MD2 overexpression could enhance the promoter activity of SpALF2 . These results revealed that Sp MD2 affects bacterial clearance by regulating AMPs. Thus, by binding to LPS and by regulating AMPs, Sp MD2 may function as a potential receptor, which is involved in the recognition and activation of a certain immune signaling pathway against Gram-negative bacteria. This study provides new insights into the diverse functions of ML proteins and into the antibacterial mechanisms of crustaceans. Highlights: Sp MD2 shared similar 3D structure with human MD2. Sp MD2 displayed strong binding activity to LPS and lipid A. Sp MD2 knockdown suppressed bacterial clearance in vivo and some AMPs' expression. Sp MD2 might function as a potential PRR involved in anti- Vibrio immunity.